The spatio-temporal dynamics of ligament healing - Chamberlain, Connie S. (2009)
Ligament injury commonly occurs with no effective treatment to restore its original state. Numerous studies have examined wound healing after injury, reporting a provisional matrix and scar formation within the wound. Few studies however report the inflammatory, proliferative, and remodeling process during ligament healing in a spatio-temporal manner. Our goal was then to more completely elucidate this process in a rat medial collateral ligament (MCL) healing model. In this study, medial collateral ligaments were surgically transected and allowed to heal. At 1, 3, 5, 7, 9, 11, 14, and 28 days postinjury ligaments were collected and examined with microangiography or immunohistochemistry. We demonstrate that neutrophils and mitotic cells peak between 1 and 5 days postinjury. The majority of factors crest between 5 and 9 days postinjury, including circulating macrophages, resident macrophages, T lymphocytes, hematopoietic cells, vascular endothelial growth factor, and blood vessels. The apoptotic cells predominate from day 9 to the end of the study (day 28). Initially, most assayed markers localize to the epiligament and to granulation tissue at the site of damage. Later, the healing region with its granulation tissue and cells continues to expand into the uninjured tissue. From these results, we have expanded current descriptions of ligament healing and offer a more complete representation of the healing process.